1995
DOI: 10.1172/jci117863
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-induced downregulation of aquaporin-2 water channel expression in rat kidney medulla.

Abstract: Lithium, a widely used treatment for bipolar affective disorders, often. causes nephrogenic diabetes insipidus. The effect of chronic lithium therapy on the expression of the vasopressin-regulated water channel Aquaporin-2 (AQP2) in rat kidney was examined. Membranes were prepared from inner medulla of one kidney from each rat, while the contralateral one was fixed for iminunofluorescence and immunoelectromnicroscopy. Immunoblotting revealed that lithium treatment reduced AQP2 expression dramatically, to 31±8%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
301
1
8

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(351 citation statements)
references
References 22 publications
41
301
1
8
Order By: Relevance
“…16 Two major effects of lithium on collecting duct-downregulating AQP-2 expression and reducing the number of renal principal cells-have been suggested to contribute to NDI. 4 Consistent with previous reports, 17 de Groot et al showed that lithium induced downregulation of AQP-2 both in cultured murine principal collecting-duct cells and in kidneys. 11 Of note, lithium initiated the proliferation of murine principal collecting-duct cells and especially increased the number of the cells in S and G2 phase of the cell cycle.…”
supporting
confidence: 88%
“…16 Two major effects of lithium on collecting duct-downregulating AQP-2 expression and reducing the number of renal principal cells-have been suggested to contribute to NDI. 4 Consistent with previous reports, 17 de Groot et al showed that lithium induced downregulation of AQP-2 both in cultured murine principal collecting-duct cells and in kidneys. 11 Of note, lithium initiated the proliferation of murine principal collecting-duct cells and especially increased the number of the cells in S and G2 phase of the cell cycle.…”
supporting
confidence: 88%
“…In 50% of these patients, chronic lithium treatment is associated with altered renal function and nephrogenic diabetes insipidus (NDI) characterized by a defective urinary concentrating mechanism that manifests in polyuria, increased sodium excretion, and hypercholoremic metabolic acidosis (3). The polyuria is largely explained by decreased abundances of the vasopressin (AVP)-regulated aquaporin 2 and aquaporin 3 (AQP2 and AQP3) water channels in the collecting duct (4,5). The renal sodium loss is likely to be caused by reduced expression of the epithelial sodium channel (ENaC) in the cortical and outer medullary collecting duct (6,7).…”
mentioning
confidence: 99%
“…UT-A1 expression is in part regulated by AVP. This would suggest that amiloride and/or inhibition of lithium uptake may have indirect effects in addition to the specific changes well documented in the collecting tubules (26,27). This is also supported by the observation that, although urinary AQP2 excretion was increased, it did not parallel the increase in urinary osmolality.…”
Section: Discussionmentioning
confidence: 98%
“…Nielsen et al have demonstrated, in animal models, that lithium inhibits AVP-stimulated insertion of AQP2 into the apical membrane due to inhibition of adenyl cyclase, which is normally activated following binding of AVP to the V 2 receptor (11,12,26). On the other hand, Deen et al have demonstrated that cAMP and AQP2 downregulation may be at least partially independent of each other (28).…”
Section: Discussionmentioning
confidence: 99%